Unsteady Numerical Investigation into the Impact of Isolator Motion on High-Mach-Number Inlet Restart via Throat Adjustment - Hongyu Tang; Yuan Liu; Yongfei Cao; Liangjie Gao; Zhansen Qian (Aerospace)
This paper focuses on exploring the variable throat-assisted restart method for high-Mach-number inlets. A two-dimensional adjustable throat hypersonic inlet was designed, and unsteady numerical simulations were carried out on its restart process, which was triggered by unstart induced by excessive back pressure and assisted by throat adjustment. The Chimera grid technique was used for grid generation, and the simulations were performed on the ARI_CFD platform. Results show that during the throat adjustment restart process, different flow states emerged with an increase in adjustment height. Specifically, when the adjustment height was too low, an unstarted flow state existed; within a specific height range (with lower and upper critical heights of 1.190 and 1.196, respectively, in this study), a fully restarted flow state occurred; and when the height was too high, an off-design flow state induced by the separation region in the internal contraction section occurred. The geometric adjustment time and throat adjustment angle also had a significant impact on the restart process. Shorter adjustment times and larger adjustment angles expanded the adjustment interval for full restart, as the rotation of the isolator helps reduce the resistance of the separation bubble’s downstream movement on the compression surface, thereby facilitating the full restart of the inlet.